2018
DOI: 10.1097/pcc.0000000000001730
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Seizures in Pediatric Extracorporeal Membrane Oxygenation Patients as Measured by Continuous Electroencephalography

Abstract: Objectives: Standards for neuromonitoring during extracorporeal membrane oxygenation support do not currently exist, and there is wide variability in practice. We present our institutional experience at an academic children’s hospital since establishment of a continuous electroencephalography monitoring protocol for extracorporeal membrane oxygenation patients. Design: Retrospective, single-center study. Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 25 publications
5
43
0
Order By: Relevance
“…In our study seizures occurred in 12 of the 50 patients (24%) which is similar to other studies. Three recent studies using continuous EEG monitoring have demonstrated that the risk for seizures in ECMO patients is substantial, with seizures detected in 18%-23% of children and 50%-83% of those having electrographic only seizures [2,16,24]. Our study further supports the indication for long-term EEG monitoring of these patients due to the high risk for electrographic only seizures.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In our study seizures occurred in 12 of the 50 patients (24%) which is similar to other studies. Three recent studies using continuous EEG monitoring have demonstrated that the risk for seizures in ECMO patients is substantial, with seizures detected in 18%-23% of children and 50%-83% of those having electrographic only seizures [2,16,24]. Our study further supports the indication for long-term EEG monitoring of these patients due to the high risk for electrographic only seizures.…”
Section: Discussionsupporting
confidence: 81%
“…Cannulation of the major vessels has a greater risk of ischemic and thromboembolic events which may account for higher neurologic injuries with VA ECMO [22,23]. However, single-center studies in both neonatal and pediatric patients have not found differences between VA, VV ECMO, and occurrence of seizures during EEG [16]. Our results may have been influenced by the fact that more than 70% of our patients were on VA ECMO.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A study of children and neonates undergoing ECMO revealed that 18% of patients had electrographic seizures, with 61% of those patients having electrographic status epilepticus and 83% having exclusively electrographic seizures [39]. Another recent study of neonatal and pediatric patients found electrographic seizures in 23% of their patients, especially within the first 24 hours of ECMO [40]. Patients with seizures had decreased survival to discharge (44% versus 74%).…”
Section: Seizuresmentioning
confidence: 99%
“…[10][11][12] Electrographic seizures are common in neonates and children undergoing extracorporeal membrane oxygenation (ECMO) and are associated with poor shortand long-term outcomes. 13,14 There are limited data to guide optimal dosing of antiseizure medications in pediatric patients undergoing ECMO, including disposition in critically ill children on ECMO. 16 Therefore, dosing adjustment may be needed.…”
mentioning
confidence: 99%